Hope is oxygen - Senie, Evan, author; Levy, EJ, advisor; Candelaria Fletcher, Harrison, advisor; Ausubel, Ramona, committee member; Khrebtan-Hoerhager, Julia, committee member (Colorado State University. Libraries, 2020)
This novel is about Jeb, Cam, and an unnamed mind character. Jeb is from Cape Cod, and he's kind of a schlub in his mid-twenties who works a job he doesn't like and drifts through unsatisfying relationships with women. He meets Cam, a bartender, also from the Cape, who struggles with depression. Jeb and Cam begin dating, which forces each of them to deal with change in their lives and a changing understanding of love. Meanwhile, the mind character observes, as he has for most of Jeb's life, making sarcastic and mocking comments, both about Jeb and the people around him. As Jeb and Cam fall in love, the mind character also falls in love vicariously and becomes aware of the possibility of becoming joined with Jeb and therefore becoming embodied and having agency. As Jeb and Cam struggle with new conceptions of love and responsibility, the mind character becomes more and more desperate to join the world, to finally have control, and to avoid losing Cam.
Keywords: depression; novel; Cape Cod; relationship; fiction